2021
DOI: 10.12659/msm.932220
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Global Impact of the COVID-19 Pandemic on Public Mental Health, with a Comparison Between the USA, Australia, and Poland with Taiwan and Thailand

Abstract: Coronavirus may have a negative impact not only on physical, but also on mental wellbeing. Despite the different approaches of countries to stop the spread of the virus and different infection rates, the dynamically developing pandemic has already affected the entire world. The consequences of the coronavirus for our mental health can be divided into those related to strategies for the prevention of infection, like isolation, quarantine, limitation of social contacts, and remote work, and those related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…Furthermore, participants in this study discussed prevalent socio-emotional challenges including fears and anxiety about COVID-19 infection in self and others, and isolation and loneliness due to prolonged social distancing. In line with these findings, other studies conducted in Thailand found that isolation due to lockdown and fears of COVID-19 infection were associated with higher rates of stress, depression, anxiety, panic, post-traumatic stress disorder, suicidal ideation, and suicide [6,59]. A large survey conducted among the Thai general population during the first lockdown found that moderate levels of anxiety and little perceived control over infection risks were associated with non-evidence based behaviour changes like food stockpiling and consumption of Vitamin C supplements [60], mirroring findings from previous pandemics [61].…”
Section: Challengessupporting
confidence: 69%
“…Furthermore, participants in this study discussed prevalent socio-emotional challenges including fears and anxiety about COVID-19 infection in self and others, and isolation and loneliness due to prolonged social distancing. In line with these findings, other studies conducted in Thailand found that isolation due to lockdown and fears of COVID-19 infection were associated with higher rates of stress, depression, anxiety, panic, post-traumatic stress disorder, suicidal ideation, and suicide [6,59]. A large survey conducted among the Thai general population during the first lockdown found that moderate levels of anxiety and little perceived control over infection risks were associated with non-evidence based behaviour changes like food stockpiling and consumption of Vitamin C supplements [60], mirroring findings from previous pandemics [61].…”
Section: Challengessupporting
confidence: 69%
“… 34 Research data from the COVID-19 pandemic demonstrate that people affected by quarantine present with stress, emotional anxiety, depression, mood swings, aggression, anger, attention deficits, hyperactivity, insomnia and post-traumatic stress. 35–43 Contrary to the reviews of cross-sectional studies, a meta-analysis of longitudinal studies and natural experiments assessing the link between the COVID-19 lockdown and mental health indicates that the initial impact of the lockdown on mental health is relatively small. Research findings suggest high mental toughness of people in response to the necessity to stay at home, lockouts and restrictions that were likewise implemented nationally or regionally around the world in response to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 95%
“…Latest research seems to confirm that people in isolation or quarantine are more likely to show significant levels of anxiety, anger, confusion and stress 34. Research data from the COVID-19 pandemic demonstrate that people affected by quarantine present with stress, emotional anxiety, depression, mood swings, aggression, anger, attention deficits, hyperactivity, insomnia and post-traumatic stress 35–43. Contrary to the reviews of cross-sectional studies, a meta-analysis of longitudinal studies and natural experiments assessing the link between the COVID-19 lockdown and mental health indicates that the initial impact of the lockdown on mental health is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Early case series on COVID-19 disease patients with syncope as the sole presenting symptom proposed autonomic failure as a potential mechanism, secondary to either direct viral effects or autoimmune/inflammatory autonomic neuropathy [ 36 ]. Neurological and psychiatric manifestations, attributed to neuroinflammation, autoimmunity, and gut-brain axis dysregulation caused by SARS-CoV-2 infection, have been increasingly reported during the COVID-19 disease pandemic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%